Avaliação autêntica para melhorar a compreensão de textos orais na primeira infância - Amancio Escalante, Pati Mariela (2021)
The objective of this research was to determine the influence of the application of authentic assessment to improve the comprehension of oral texts in the students of the II cycle of the Experimental College of the province of Lima, Peru. The design used is quasi-experimental, there was a sample of 50 students between boys and girls aged 5 and 6, distributed into 25 boys and girls for the control group and 25 for the experimental group, the data were collected by of an Adhoc questionnaire of 16 items based on the dimensions, inference, reflection, recovery and organization and active listening, likewise the instrument was submitted to expert judgment fulfilling the essential requirements, which are (0.82) of high validity , reliability and objectivity. Cronbach's Alpha coefficient has an average index reached per item of 0.907. It was concluded affirming that the application of authentic assessment significantly influences the comprehension of oral texts of the students of the second cycle of the sample in question, favoring the development of the comprehension of oral texts in boys and girls of early childhood, having as a product the quality performances of oral comprehension.